Teaching dossier guidance for professional faculty: an evidence-based approach for demonstrating teaching effectiveness - Taylor, Samantha; Charlebois, Sylvain (Frontiers in Education, 2024)
This research delves into the challenging paradox facing university faculty: they are often hired with minimal formal teacher training yet must exhibit teaching effectiveness when seeking promotion or tenure. This issue becomes particularly salient for educators with non-traditional, professional backgrounds who must demonstrate pedagogical competence despite lacking conventional academic training. This study examines teaching dossier guidelines employed by prominent universities that hire permanent teaching-focused business faculty who may have diverse, non-traditional backgrounds. For example, a Chartered Professional Accountant who trained in a public accounting firm and worked as a Chief Financial Officer of a public energy company or a sales executive who led the business development department of a large company likely do not possess the same academic training of a doctorate degree like other academics; however, such professional faculty may possess relevant experience and skills to teach accounting to post-secondary students effectively. Our analysis identifies recurring recommendations for faculty to incorporate into their teaching dossiers, encompassing elements such as summaries of teaching responsibilities, documentation of course development or modification, creation of instructional materials, ongoing pedagogical improvement endeavours, outstanding teaching materials, articulation of teaching philosophies, and evidence of collegial collaboration and support. Our findings reveal a disconnect in understanding and recognizing the significance of teaching and teaching dossiers. In light of these observations, this paper outlines the limitations inherent in the current system. It suggests promising avenues for future research within this domain. We aim to foster a more equitable and supportive environment for all faculty members engaged in the complex task of academic teaching.